ETIMOLOGI STUDI ISLAM - ihsan, hayatul (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2016)
Etymologically Islamic Studies is a translation of theArabic Dirasah Islamiyah. While Islamic Studies in the westknown as the Islamic Studies. Then Islamic studies are literallythe study on matters related to Islam. This meaning is socommon that there needs to be understanding terminologicalspecification of Islamic studies in a systematic and integratedstudies. Of social phenomena that occur in society, Islam isattractive to serve as the object of study and in studying Islam,surely we must be guided by two authentic sources of the Qur'anand the hadith. The relationship between the two can not beseparated, but are clearly distinguishable. Their relationshipdoes not stand alone and face to face, but both woven,intertwined and interwoven such that both together in onewholeness solid and compact. The deepest meaning andmoralitaskeagamaan still there, still emphasized and underlinedin understanding the vagaries of the phenomenon of humandiversity, then he automatically can not escape from the chainsand pitfalls of space and time.